A high-throughput model for screening anti-tumor agents capable of promoting polymerization of tubulin in vitro - HU Wei; DONG Hui; LI Yue-zhong; HU Xi-tao; HAN Guan-jun; QU Yin-bo (Acta Pharmacologica Sinica, 2016)
AIM: To establish a high-throughput model for screening anti-tumor agents capable of promoting the polymerization of tubulin in vitro. METHODS: Tubulin was prepared in different purity for two screening steps. The first step was a high-throughput screening (HTS) for a set of 1500 samples using the GTP-containing tubulin and the end-reading method. The second step was performed on 119 hits from the first screening by a kinetic assay with GTP-lacking tubulin. RESULTS: The HTS for 1500 samples was accomplished in less than 3 h. From the screening, 108 samples were identified with >20 % promotion activity at 10 mg/L. Five of 108 were further confirmed by the kinetic assay using the purified tubulin subsequently. Three of the hit compounds were Epothilone A or its analogs, the other two compounds had new structures with a common pharmacophore for cytotoxic natural products that stabilize microtubules. In an MTT test, the five selected samples from the screening showed a minimal IC(50) at 0.28+/-0.06 nmol/L to Hela cells. CONCLUSION: The two-step screening method is a high-throughtput, cost-effective, and efficient approach to identify microtubule-stabilizing agents.